KETERKAITAN STRUKTUR KOMUNITAS MEIOFAUNA DENGAN KERAPATAN LAMUN DAN PARAMETER LINGKUNGAN DI SELAT DOMPAK, KEPULAUAN RIAU - Zulkifli, Zulkifli; Soedharma, Dedi; Wardiatno, Yusli; Sanusi, Harpasis S. (Jurnal Perikanan dan Kelautan, 2007)
A study on the relationship between meiofauna community structure with seagrassdensity and environmental parameters has been carried out in the Dompak Straitwaters, Riau Archipelago. This study were investigated on four different seasonsthroughout a year, from May 2005 to April 2006. Three sampling site, i.e.., Al, A2and A3 were chosen to represent research sites. The sediment samples were tekenby PVC cores, in which six layers were separated (i.e. 0-5 cm, 5-10 cm, 10-15 cm,15-20 cm, 20-25 cm and 25-30 cm). The environmental parameters, such ascurrent velocity, the sediment composition, total organic carbon (TOO, totalorganic matter (TOM), pH and redox potential (Eh), were also observed. The dataon meiofauna, seagrass density and environmental parameters were analyzedstatistically by a regression analyisis. This analysis was run using a SPSS softwareversion 11.5 for Windows. The meiofauna was dominated by Nematodes,Copepods, Polychaetes, Foraniiniferans and Turbellarians. The results areshowing that the meiofaunal community structure would depend on severalconditions such as seagrass density, environmental factors and hydrologicalcharacteristics. The regression results are showing that the meiofaunal communitystructure patterns was significantly correlated with seagrass density and to theenvironmental parameters. Vertically, the meiofaunal community structurepatterns seems to be more affected by TOC and TOM. While the horizontally, itseems to he more affected by current velocity, TOM and pH.